If it's not what You are looking for type in the equation solver your own equation and let us solve it.
c in (-oo:+oo)
(4*c)/3 = 6*c-112 // - 6*c-112
(4*c)/3-(6*c)+112 = 0
(4*c)/3-6*c+112 = 0
112-14/3*c = 0 // - 112
-14/3*c = -112 // : -14/3
c = -112/(-14/3)
c = 24
c = 24
| 7y-2.2=3y | | 5/12(x-5)=3 | | 18.2x=1820 | | 2n+(-6)=2n-5 | | 1/4x3/7x4/5= | | 8x-3x+99=8x+36 | | 11c-16=-6-c+12c | | 7a/=4a-117 | | 6b+3b+14= | | 5n/4=4n-44 | | 5w^2+2w-7=0 | | 54-11x=16+8x | | x+0.75x=91 | | 4w-63=7w/4 | | -11+10p+100=4-10p-11 | | 10x-5=x-2 | | 5z/3=3z-20 | | 5x^2-10=25 | | 24+30x= | | 11z=8+10 | | 7x-5=2(3x+9) | | 3x+5x-3=-19 | | 0.2x(x+3)-4(2x-3)=0.9 | | y+258=-8y-3 | | 7.50+2.50b=12.50 | | (4x-12)/7 | | (X+3)2+(6x)=46 | | 7x=-5+2(3x+9) | | S-12=47 | | y-13=0(x-4) | | 4x-12/7 | | -3.8s-6.92=19.96+2.6s |